HYDRODYNAMIC EXPERIMENTS AND MODELING IN ARTIFICIAL FLUME USED FOR AQUACULTURE - Fauzan Iskandar, Rifqi
Various kinds of research have been conducted to obtain the most efficient and effective conditions in aquaculture activities. In this study, hydraulic modeling was carried out on an artificial flume in the form of a closed path. The driving source in this study is a paddlewheel aerator with two pedals. From the results of measuring the flow velocity using the Sontek Argounat ADV and Sontek Handheld tools on the channel, it was found that along the channel the flow velocity can be read from the surface to the bottom of the channel. The average flow velocity measured is 0.077 m/s. This proves that there is an even circulation of flow along the channel. The flow pattern formed and the velocity as well as the flow velocity in the channel were then compared with a numerical model using Delft3D. From this comparison, it is necessary to have a correction value between the discharge that occurs in the channel and the input parameter of the discharge in the Delft3D model. By using the t-test method, the correction value between field discharge and model discharge is 1.26. However, the distribution of flow velocity in the bends of the Delft3D model does not describe the flow pattern according to field conditions. In addition, the purpose of this study is to obtain a reduction coefficient between the rotational speed of the aerator on the aerator and the flow velocity. From the number of rotations of the wheel at 90 rpm, the rotational speed of the wheel that occurs is 3.06 m/s. So that the coefficient of the reduction factor of the speed of the paddlewheel to the flow velocity is 3.99.